Pre-analytics of pathological specimens in oncology - Dietel, Manfred; Wittekind, Christian; Bussolati, Gianni; Winterfeld, Moritz von (Recent results in cancer research, 2015)
This book presents an overview of the most important current developments in the pre-analytical handling of tissue. It addresses in particular potential ways to improve the situation whereby methods employed in the pre-analytical phase - the period from surgical removal of tissue to the start of pathological processing - have remained essentially unchanged for decades with only modest standardization. It is examined how the pre-analytical period can be optimized, resulting not only in an increase in diagnostic quality but also in a reduction in processing time and costs. Among the key topics examined are the so-called cold ischemia time between tissue removal and fixation, the potential superiority of vacuum-based preservation over immediate formalin fixation, two-temperature fixation, molecular analysis methods, and the pre-analytics of specimens from particular tissues. Readers will find this book to be an important update that reveals the full importance of the pre-analytical phase for quality of pathological work-up
Description based upon print version of record